Efficacy of preoxygenation using tidal volume breathing: a comparison of Mapleson A, Bain's and Circle system - Suman Arora; Priyanka Gupta; Virender Kumar Arya; Nidhi Bhatia (Revista Brasileira de Anestesiologia)
Abstract Background: Efficacy of preoxygenation depends upon inspired oxygen concentration, its flow rate, breathing system configuration and patient characteristics. We hypothesized that in actual clinical scenario, where breathing circuit is not primed with 100% oxygen, patients may need more time to achieve EtO2 ≥ 90%, and this duration may be different among various breathing systems. We thus studied the efficacy of preoxygenation using unprimed Mapleson A, Bain's and Circle system with tidal volume breathing at oxygen flow rates of 5 L.min−1 and 10 L.min−1. Methods: Patients were randomly allocated into one of the six groups, wherein they were preoxygenated using either Mapleson A, Bain's or Circle system at O2 flow rate of either 5 L.min−1 or 10 L.min−1. The primary outcome measure of our study was the time taken to achieve EtO2 ≥ 90% at 5 and 10 L.min−1 flow rates. Results: At oxygen flow rate of 5 L.min−1, time to reach EtO2 ≥ 90% was significantly longer with Bain's system (3.7 ± 0.67 min) than Mapleson A and Circle system (2.9 ± 0.6, 3.3 ± 0.97 min, respectively). However at oxygen flow rate of 10 L.min−1 this time was significantly shorter and comparable among all the three breathing systems (2.33 ± 0.38 min with Mapleson, 2.59 ± 0.50 min with Bain's and 2.60 ± 0.47 min with Circle system). Conclusions: With spontaneous normal tidal volume breathing at oxygen flow rate of 5 L.min−1, Mapleson A can optimally preoxygenate patients within 3 min while Bain's and Circle system require more time. However at O2 flow rate of 10 L.min−1 all the three breathing systems are capable of optimally preoxygenating the patients in less than 3 min.